New Trends in Human Resource Management: A Literature Review on Millennials and Gen Z - Rabbiyanti, Dila Kurnia; Hafidli, Dedih; Tambunan, Hasudungan Budi Doppak; Suryanto, Yayan; Gumilang, Irlan Karsa (LPPM Universitas Bina Bangsa, 2025)
The demographic shift in the workforce, marked by the increasing presence of Millennials and Generation Z, has significantly transformed human resource management (HRM) practices. This literature review explores recent trends in HRM strategies tailored to address the unique characteristics, values, and work expectations of these generations. Millennials and Gen Z prioritize work-life balance, inclusivity, flexibility, and meaningful engagement at work, demanding organizations to innovate managerial approaches, embrace digital technologies, and foster more agile leadership styles. The study synthesizes findings from both Indonesian and international journals to identify critical HRM adaptations, such as personalized employee engagement, hybrid work systems, and value-driven career development. Challenges related to managing multigenerational workforces and prospects for sustainable talent retention are also discussed. This review provides comprehensive insights to help organizations develop dynamic, technology-enabled, and human-centered HRM strategies that effectively attract, motivate, and retain Millennial and Gen Z talent in today’s competitive business environment.